Etika Rasionalisme Versus Etika Voluntarisme (Studi Kritis Mu’tazilah Dan Asy’ariyah) - Havis Aravik; Choiriyyah Choiriyyah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2018)
Abstract: This study discusses the ethics of rationalism versus voluntarism ethics, where morals in principle have been debated by experts for a long time, among them Mu'tazilah with the ethics of rationalism and Ash'ariyah with voluntary ethics. For the Mu'tazila morality is a rational act of man in seeing which is good and what is bad, not merely determined by the demands of religion. While Asy'ariyah holds the opposite view that morality is under the control of God or with another understanding that morality presupposes religion. Keywords: Ethics, Rationalism, Voluntarism, Mu'tazilah, Asy'ariyah Abstrak: Studi ini membahas tentang etika rasionalisme versus etika voluntarisme, di mana moral pada prinsipnya telah menjadi perdebatan para ahli kalam sejak lama, di antaranya Mu’tazilah dengan etika rasionalisme dan Asy’ariyah dengan etika voluntarisme. Bagi Mu’tazilah moralitas adalah sebuah tindakan rasional manusia dalam melihat mana yang baik dan mana yang buruk, tidak semata ditentukan oleh tuntutan agama. Sedangkan Asy’ariyah berpandangan sebaliknya bahwa moralitas berada di bawah kontrol Tuhan atau dengan pengertian lain moralitas itu mengandaikan agama. Kata Kunci; Etika, Rasionalisme, Voluntarisme, Mu’tazilah, Asy’ariyah DOI: 10.15408/sjsbs.v5i1.7902